Time management and business performance among bumiputera entrepreneurs / Fidelis Rexy Albert - Albert, Fidelis Rexy (2016)
Commitment is about the state or quality of being dedicated to an activity. The study aimed to determine the level of commitment in time management among Bumiputera entrepreneurs. The specific objectives of this study are to determine the level of commitment in time management among Bumiputera entrepreneurs, to assess the relationship between commitment in time management and Bumiputera entrepreneurs' business performance and to recommend the strategy on how to improve business performance among Bumiputera entrepreneurs. There are some problems with some Bumiputera Entrepreneurs where they are not committed enough when doing business, especially in terms of time management.